Career assessment and creativity: potential complementarity or a contradiction in terms?. Issue 1 (2nd January 2020) - Watson, Mark; McMahon, Mary
ABSTRACT: In this research we investigated whether creativity and career assessment are a contradiction in terms or whether, through creative thinking, their potential complementarity in career guidance and counselling can be realised. The research demonstrates the creative application of the systemic Integrative Structured Interview (ISI) for the Self-Directed Search (SDS) with a South African female mid-life career changer. Results indicated that the ISI positions clients as storytellers who create rich systemic stories about their quantitative SDS scores. The constructs of story telling are evident throughout an interview about quantitative scores; the scores become unifying themes across the stories. In sum, the ISI can assist mid-life career changers to make meaning of their career transition; and by embedding career assessment in a systemic story telling process creativity is evidenced as a multilayered process.